A novel second-stage surgical strategy for severely obese patient with pancreatic neuroendocrine tumor: a case report - Akira Umemura; Akira Sasaki; Hiroyuki Nitta; Hirokatsu Katagiri; Shoji Kanno; Daiki Takeda; Taro Ando; Satoshi Amano; Masao Nishiya; Noriyuki Uesugi; Tamotsu Sugai (Surgical Case Reports)
Abstract Background Severely obese patients can have other diseases requiring surgical treatment. In such patients, bariatric surgeries are considered a precursor to operations targeting the original disease for the purpose of reducing severe perioperative complications. Pancreatic ectopic fat deposition increases pancreas volume (PV) and thickness, which can worsen insulin resistance and islet β cell function. To address this problem, we present a novel two-stage surgical strategy performed on a severely obese patient with pancreatic neuroendocrine tumor (PNET) consisting of laparoscopic sleeve gastrectomy (LSG) as a metabolic surgery followed by laparoscopic spleen-preserving distal pancreatectomy (LSPDP). Case presentation A 56-year-old man was referred to our hospital for further investigation of a pancreatic tumor. His initial body weight and body mass index (BMI) were 94.0 kg and 37.2 kg/m2, respectively. Contrast computed tomography revealed an enhanced tumor measuring 15 mm on the pancreatic body. The pancreas thickness and PV were 32 mm and 148 mL, respectively. An endoscopic ultrasonographic fine needle aspiration identified the tumor as PNET-G1. We first performed LSG, the patient’s body weight and BMI had decreased dramatically to 64.0 kg and 25.3 kg/m2 at 6 months after LSG. The pancreas thickness and PV had also decreased to 17 mm and 99 mL, respectively, with no tumor growth. Since LSG has been shown to reduce the perioperative risk factors of LSPDP, and to improve insulin resistance and recovery of islet β cell function, we performed LSPDP for PNET-G1 as a second-stage surgery. The postoperative course was unremarkable, and the patient was discharged on postoperative day 14 without symptomatic postoperative pancreatic fistula (POPF). He was followed without recurrence or type 2 diabetes (T2D) onset for 6 months after LSPDP. Conclusions We present a novel two-stage surgical strategy for a severely obese patient with PNET, consisting of LSG as a metabolic surgery for severe obesity, followed by LSPDP after confirmation of good weight loss and metabolic effects. LSG before pancreatectomy may have a potential to reduce pancreas thickness and recovery of islet β cell function in severely obese patients, thereby reducing the risk of clinically relevant POPF and post-pancreatectomy T2D onset.